Strategi Komunikasi Radio Citra FM Kendal Dalam Meningkatkan Minat Pendengar - Miftahul Huda; Sarinah Sarinah; Viro Dharma Saputra (Journal of Communication Studies, 2021)
Abstract Radio is a communication medium that emerged in the telecommunications era. Radio as a medium of communication provides convenience for the public to obtain information. Along with the development of high information technology, radio has various challenges to maintain its existence. This study aims to determine the communication strategy used by Radio Citra in increasing listener interest. In this study, using the post-positivist paradigm, and including the type of qualitative research. This study uses three data collection techniques, namely observation, interviews, and documentation. The data analysis technique in this study used the stages of data reduction, data presentation, and drawing conclusions. The results of this study are that Citra radio's strategy in increasing listener interest is by packaging interesting programs, using social media Facebook, Instagram and streaming for broadcasts, functioning broadcasters as the spearhead and heart, actively engaging the community directly, and using conformity strategies. Radio Citra also makes careful program planning, makes program productions, executes programs to broadcast programs according to a predetermined plan, and conducts monitoring and evaluation.